1177. Carbapenemase-Producing Carbapenem-Resistant Organism Colonization Screening Surveys, Maryland, April 2017–April 2018. (26th November 2018) - Brooks, Richard B; Vaeth, Elisabeth; Jani, Niketa M; Dominguez, Catherine E; Johnston, Jonathan R
Abstract: Background: In April 2017, the Maryland Department of Health (MDH) began screening healthcare contacts of confirmed cases of carbapenemase-producing carbapenem-resistant organisms (CP-CROs) to identify potential transmission, per guidance published by the Centers for Disease Control and Prevention. The results of MDH's CP-CRO colonization screening surveys (CSSs) conducted as of April 1, 2018, are summarized. Methods: Rectal swabs were collected on epidemiologically linked CP-CRO contacts and sent to the MDH Laboratories Administration, where the Cepheid Xpert® Carba-R assay was used to detect five carbapenemases: Klebsiella pneumoniae carbapenemase (KPC), New Delhi metallo-β-lactamase (NDM), Verona integron encoded metallo-β-lactamase (VIM), imipenemase (IMP), and oxacillinase-48-like carbapenemase (OXA-48). Identification of CP-CROs in contacts sometimes resulted in additional CSSs to ensure complete case detection. Non-KPC cases were combined for analysis. Results: During April 1, 2017–April 1, 2018, MDH received reports of 278 incident cases of confirmed CP-CROs. Of these, 16 (6%) expressed non-KPC carbapenemases. The 7 (3%) cases with healthcare contacts prompting CSSs led to screening of 132 first-round contacts, with additional CP-CROs identified in 13 (10%), all of which had KPC. Of these, 12 (92%) resided in ventilator units of skilled nursing facilities (vSNFs). In the first-round CSS at one vSNF, 64% of screened contacts were positive for KPC, which had not been identified in the index case. Weekly follow-up CP-CRO admission screenings and serial follow-up CSSs at the vSNF resulted in screening of a total of 72 unique patients; 38 (53%) were KPC-positive. Of these 38 cases, 32 (89%) were previously unidentified and were placed on contact precautions if not already on them. Staff were re-trained in infection prevention (IP) techniques, and staff and KPC-positive patients were cohorted. Conclusion: Detection of CP-CROs that express non-KPC carbapenemases in Maryland is rare, and transmission of these carbapenemases has not been identified. However, CSSs identified previously unknown cases of KPC, most commonly in vSNFs, demonstrating the utility of CSSs to detect CP-CROs, and resulting in important IP interventions. Disclosures: All authors: No reported disclosures.